Метод керування вентильним електродвигуном за допомогою ШІМ сигналів - Хроменко, А. Г. (ХНУРЕ, 2021)
This paper describes a method for controlling rectified electric motors and drives based on them, using PWM signals generated by a microcontroller. The regulation algorithm is described, and the creation of a control unit based on this algorithm. The main advantages of this method are shown, the expediency and relevance of its use in the aviation industry, and electro-mechanical units with an increased degree of reliability are proved.
Keywords: вентильний електродвигун